Improving Mekong dam dialogues: a participatory assessment of the impact of dams on the livelihoods of the Mekong - Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
Uses the thaibaan research methodology (called 'sao ban' in Laotian), a participatory process for video production to help villagers explore the positive and negative impacts of dams outside the immediate dam area. The output is a series of short films and documentaries made by communities, and which can then be used to table community perspectives in hydropower decision-making.